2006
DOI: 10.1111/j.1365-2982.2006.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an acute intraluminal administration of capsaicin on oesophageal motor pattern in GORD patients with ineffective oesophageal motility

Abstract: Ineffective oesophageal motility (IOM) is a functional disorder affecting about 50% of gastro-oesophageal reflux disease (GORD) patients. This disease in a severe form limits the clearing ability of the oesophagus and is considered one of the predictive factors for poorer GORD resolution. Capsaicin, the active compound of red pepper, exerts a prokinetic effect on oesophageal motility in healthy subjects by increasing the amplitude of body waves, even if no evidence exists on its possible role in situations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
3
20
1
Order By: Relevance
“…That there is a role for TRPV1 and other TRP channels in sensory signalling from the bowel and other organs is clear. This role extends, as shown in the study by Grossi et al ., 13 to dysmotility and sensation. Although a direct role in pathophysiology is not proven, this is not a negative observation with respect to therapeutic potential for modulators of these receptors.…”
Section: A Role For Trp Channels In Sensitivity and Hypersensitivitysupporting
confidence: 86%
“…That there is a role for TRPV1 and other TRP channels in sensory signalling from the bowel and other organs is clear. This role extends, as shown in the study by Grossi et al ., 13 to dysmotility and sensation. Although a direct role in pathophysiology is not proven, this is not a negative observation with respect to therapeutic potential for modulators of these receptors.…”
Section: A Role For Trp Channels In Sensitivity and Hypersensitivitysupporting
confidence: 86%
“…This was not the case, and our findings are consistent with those of Lemme et al, who found that the proportion of low-amplitude swallows did not differ between IOM patients with erosive versus non-erosive GORD [23] . It is feasible that the presence of propagating (albeit low-amplitude) sequences equates to more efficient clearance [24] of refluxate in these patients, and novel approaches to stimulating clearance [25] may prove beneficial in this IOM subset. Another explanation for the high heartburn prevalence is that these patients exhibit oesophageal hypersensitivity [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Acute ingestion of capsaicin has a protective effect against aspirin-induced erosions in the gastric mucosa of human volunteers (Yeoh et al, 1995). In addition, capsaicin can improve esophageal motility in patients with gastro-esophageal reflux disease (Grossi et al, 2006). Prolonged intake of capsaicin appears to desensitize afferent nerve fibers against noxious stimulation of the upper GI tract.…”
Section: Expression and Functional Implications Of Trp Channels In Thmentioning
confidence: 99%